Imagens simbólicas da conquista da Terra dos Brasis - Assunção, Paulo de (Revista de História, 1997)
The conquest of Brasis Land shows us the necessity of the integration of the new lands in the european context of the XVI century. The study of religious symbolic images, done by the first Jesuits, allows us to understand the reach of the ideas that were used to explain the complex universe of the relationship between Europe and America. The differences and similarities were comprehended by means of biblical examples, which reveal the reading mechanisms of superiority and inferiority, that characterized the cultural interaction and the power relation in the XVI century.